Impacto socioeconómico de la pandemia covid-19 en las familias de la ciudadela Colinas del Sur del cantón Pasaje, año 2021 - Guzmán Tene, Elena Magaly; Maldonado Aguirre, Mónica Alexandra (Machala, 2021)
This research aims to demonstrate the socioeconomic conditions produced by the COVID-19 pandemic in families and the effects caused in health, education, changes that have occurred in family relationships, conflicts and layoffs in the labor field as a result of the preventive and mandatory social isolation decreed by the National COE in the state of emergency. The main objective of the research is to determine the socioeconomic impact produced by COVID-19 on the families of the Colinas del Sur neighborhood through surveys and interviews to identify the consequences of the problem. The specific objectives are to identify the productive and commercial activities that have been affected by the pandemic; as well as to specify the social changes that families have experienced in their daily lives; likewise to distinguish the local community problems that aggravate the situation generated by the pandemic and to establish the programs that the Ministry of Public Health (MSP) has implemented in the face of the health emergency. The hypothesis is that the families of the Colinas del Sur neighborhood have been affected by COVID-19, with a decrease in their economic income, reduction of sources of work, increase in labor informality, increase in the poverty index, increase in intra-family conflicts, inequalities in access to education and health affectation. The research used an empirical-inductive epistemological approach based on the theoretical perspective of critical theory, with a quantitative-qualitative methodological approach and the techniques used for data collection were the following: survey, interview and observation guide. The surveys were applied to the total population of 212 heads of household who contributed with relevant information that was later analyzed, interpreted and statistically represented. The interviews were applied to key authorities of the Cantonal COE, as well as to the chief of police of the UPC that has jurisdiction in the town studied and to the director of the Loma de Franco health sub-center to which the Colinas Sur town belongs, to gather important information on how the Emergency Operations Committee (COE) proceeded, what were its actions, strategies, management and difficulties that arose during the health emergency. Likewise, we used observation guides to verify the reality of the place and the homes of the locality studied, using biosecurity and social distancing protocols to safeguard the health and prevent the contagion of the academic pair in charge of the research and of the population studied due to the COVID-19 pandemic. Being a descriptive, explanatory and propositive research in a first moment it analyzed the previous researches related to the subject, it approached the scenarios in which the research was developed and with the results obtained from the application of techniques and research instruments we proceeded to the creation of a proposal that contributes to the generation of entrepreneurship through a community socio-family entrepreneurship program in the Colinas del Sur neighborhood that with the commitment of the Pro-improvements Committee, the GAD Cantonal de Pasaje, governmental institutions and the citizenship; through the use of the potentialities of the sector become sources of employment and this will help to improve the economy of families and in turn contribute to improving the quality of life of people.
La presente investigación pretende evidenciar las condiciones socioeconómicas producidas por la pandemia COVID-19 en las familias y los efectos causados en la salud, educación, los cambios que se han dado en las relaciones familiares, los conflictos y despidos en el campo laboral producto del aislamiento social preventivo y obligatorio decretado por el COE Nacional en el estado de excepción. El objetivo central de la investigación se orienta a determinar el impacto socioeconómico producido por el COVID-19 en las familias de la ciudadela Colinas del Sur a través de encuestas y entrevistas para identificar las consecuencias de la problemática. Los objetivos específicos se disponen a identificar las actividades productivas y comerciales que se han visto afectadas por la pandemia; así como a especificar los cambios sociales que han experimentado las familias en su cotidianidad; del mismo modo a distinguir los problemas comunitarios locales que agravan la situación generada por la pandemia y establecer los programas que el Ministerio de Salud Pública (MSP) ha implementado ante la emergencia sanitaria. La hipótesis es que las familias de la ciudadela Colinas del Sur han sido afectadas por el COVID-19 teniendo una disminución en sus ingresos económicos, reducción de fuentes de trabajo, incremento de la informalidad laboral, aumento del índice de pobreza, aumento de conflictos intrafamiliares, desigualdades en el acceso a la educación y afectación de la salud. Para la investigación se utilizó el enfoque epistemológico empírico-inductivo basado en la perspectiva teórica de la teoría crítica, con un enfoque metodológico cuanti-cualitativo y las técnicas utilizadas para la recolección de datos fueron las siguientes: encuesta, entrevista y guía de observación. Las encuestas se aplicaron al total de la población siendo 212 jefes de hogar que contribuyeron con información relevante que posteriormente fue analizada, interpretada y representada estadísticamente, las entrevistas fueron aplicadas a autoridades claves del COE Cantonal, así también al jefe de policía del UPC que tiene jurisdicción en la ciudadela estudiada y a la directora del Subcentro de salud Loma de Franco al que pertenece la ciudadela Colinas Sur para recabar información importante sobre como procedió el Comité de Operaciones de Emergencia (COE), cuáles fueron sus acciones, estrategias, gestiones y dificultades que se le presentaron ante la emergencia sanitaria. Del mismo modo recurrimos a las guías de observación para constatar la realidad del lugar y de los hogares de la localidad estudiada, utilizando protocolos de bioseguridad y de distanciamiento social para salvaguardar la salud y prevenir el contagio del par académico encargado de la investigación y de la población estudiada por motivo de la pandemia del COVID-19. Siendo una investigación descriptiva, explicativa y propositiva en un primer momento analizó las anteriores investigaciones relacionadas al tema, abordó los escenarios en los que se desarrolló la investigación y con los resultados obtenidos de la aplicación de técnicas e instrumentos de investigación se procedió a la creación de una propuesta que tribute a la generación de emprendimientos a través de un programa de emprendimiento sociofamiliar comunitario en la ciudadela Colinas del Sur que con el compromiso del Comité Pro-mejoras, el GAD Cantonal de Pasaje, instituciones gubernamentales y la ciudadanía; mediante el aprovechamiento de las potencialidades que posee el sector se conviertan en fuentes de empleo y esto coadyuve a mejorar la economía de las familias y a su vez contribuya a mejorar la calidad de vida de las personas.
Keywords: IMPACTO; PANDEMIA; SOCIO-ECONOMICO